A comprehensive assessment of the transcriptome of cork oak (Quercus suber) through EST sequencing. - Pereira-Leal, José B; Abreu, Isabel a; Alabaça, Cláudia S; Almeida, Maria Helena; Almeida, Paulo; Almeida, Tânia; Amorim, Maria Isabel; Araújo, Susana; Azevedo, Herlânder; Badia, Aleix; Batista, Dora; Bohn, Andreas; et al. (BMC genomics, 2014)
BACKGROUND: Cork oak (Quercus suber) is one of the rare trees with the ability to produce cork, a material widely used to make wine bottle stoppers, flooring and insulation materials, among many other uses. The molecular mechanisms of cork formation are still poorly understood, in great part due to the difficulty in studying a species with a long life-cycle and for which there is scarce molecular/genomic information. Cork oak forests are of great ecological importance and represent a major economic and social resource in Southern Europe and Northern Africa. However, global warming is threatening the cork oak forests by imposing thermal, hydric and many types of novel biotic stresses. Despite the economic and social value of the Q. suber species, few genomic resources have been developed, useful for biotechnological applications and improved forest management. RESULTS: We generated in excess of 7 million sequence reads, by pyrosequencing 21 normalized cDNA libraries derived from multiple Q. suber tissues and organs, developmental stages and physiological conditions. We deployed a stringent sequence processing and assembly pipeline that resulted in the identification of ~159,000 unigenes. These were annotated according to their similarity to known plant genes, to known Interpro domains, GO classes and E.C. numbers. The phylogenetic extent of this ESTs set was investigated, and we found that cork oak revealed a significant new gene space that is not covered by other model species or EST sequencing projects. The raw data, as well as the full annotated assembly, are now available to the community in a dedicated web portal at http://www.corkoakdb.org. CONCLUSIONS: This genomic resource represents the first trancriptome study in a cork producing species. It can be explored to develop new tools and approaches to understand stress responses and developmental processes in forest trees, as well as the molecular cascades underlying cork differentiation and disease response.
APS
Keywords: Cork oak; EST sequencing; Quercus suber; transcriptome

miRNA profiling in leaf and cork tissues of Quercus suber reveals novel miRNAs and tissue-specific expression patterns - Chaves, Inês; Lin, Yao-Cheng; Pinto-Ricardo, C; de Peer, Yves; Miguel, Célia (TREE GENETICS & GENOMES, 2014)
The differentiation of cork (phellem) cells from the phellogen (cork cambium) is a secondary growth process observed in the cork oak tree conferring a unique ability to produce a thick layer of cork. At present, the molecular regulators of phellem differentiation are unknown. The previously documented involvement of microRNAs (miRNAs) in the regulation of developmental processes, including secondary growth, motivated the search for these regulators in cork oak tissues. We performed deep sequencing of the small RNA fraction obtained from cork oak leaves and differentiating phellem. RNA sequences with lengths of 19-25 nt derived from the two libraries were analysed, leading to the identification of 41 families of conserved miRNAs, of which the most abundant were miR167, miR165/166, miR396 and miR159. Thirty novel miRNA candidates were also unveiled, 11 of which were unique to leaves and 13 to phellem. Northern blot detection of a set of conserved and novel miRNAs confirmed their differential expression profile. Prediction and analysis of putative miRNA target genes provided clues regarding processes taking place in leaf and phellem tissues, but further experimental work will be needed for functional characterization. In conclusion, we here provide a first characterization of the miRNA population in a Fagacea species, and the comparative analysis of miRNA expression in leaf and phellem libraries represents an important step to uncovering specific regulatory networks controlling phellem differentiation.
Keywords: miRNA; phellem; Quercus suber; secondary growth; Small RNA; Tree

Temperature stress effects in Quercus suber leaf metabolism. - Chaves, Inês; Passarinho, José António P; Capitão, Cláudio; Chaves, Maria Manuela; Fevereiro, Pedro; Ricardo, Cândido P P (Journal of plant physiology, 2011)
Based on projections that climate changes are will intensify in the near future, it is important to understand how plants respond to climate. Consequently, we have been studying the effect of contrasting temperatures on leaf metabolism of Quercus suber, an important Mediterranean oak. Potted plants were grown under controlled conditions for 53 days at 28°C or 10°C. The accumulation of major soluble metabolites was analyzed by NMR. The relative levels of transcripts of genes encoding key enzymes of the shikimate and phenylpropanoid pathway (CS, PAL, CAD and ChS) were examined by means of quantitative, real-time RT-PCR. At 10°C, in the pre-existing leaves, the concentrations of sucrose, quercitol and catechin were higher, as were PAL and ChS transcripts. At 28°C, however, it was the concentration of quinic acid that was higher, as were the concentrations of CS and CAD transcripts. We conclude that contrasting temperatures greatly influence Q. suber metabolism and that a deeper analysis of the effects of more extreme temperatures is needed to understand the possible effects of temperature changes on Q. suber metabolism and physiology.
Keywords: Abiotic stress response; Cork oak; Phenol metabolism; Secondary metabolism